Strategies for Supporting Critical Thinking Skills in Children by Preschool Teachers Scale: Validity and Reliability Study - Yaralı, Kevser Tozduman; Kavruk, Sevinç Zeynep; Ceyhan, Görkem; Saçan, Selvinaz (My University, 2024)
The aim of this study is to develop a measurement tool to determine the strategies of preschool teachers in supporting critical thinking skills in children. In the research, 300 preschool teachers participated in the exploratory factor analysis (EFA) and 390 preschool teachers participated in the confirmatory factor analysis (CFA). In the study conducted with a survey model, the scale is a 5-point Likert type and consists of a single factor. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were performed for the construct validity of the scale. The variance explained by the single-factor structure is 69%, with factor loadings ranging from 0.695 to 0.894. When the fit indices of the scale were examined, the RMSEA value was found to be 0.071, the SRMR value was 0.061, the CFI value was 0.99, the NFI was 0.98, the NNFI was 0.99, and the ?²/df was 2.84. The Cronbach's Alpha value, calculated for the reliability of the measurement results obtained from the main application of the scale, was found to be 0.97, while the reliability coefficient obtained for the Spearman-Brown Split-Half method was determined to be 0.98. As a result, it can be stated that the \"Strategies for Supporting Critical Thinking Skills in Children by Preschool Teachers Scale\" is a valid and reliable scale that can be used to determine the strategies of teachers in supporting critical thinking skills in children.
Keywords: Validity; Reliability; Critical thinking; Higher-order thinking; Preschool period